ショウワ キチ シュウヘン デ ホカク シタ 5 トウ ノ ウェッデルアザラシ ノ ガイブ ケイタイ ト ゾウキ ジュウリョウ - 藤瀬, 良弘; フジセ, ヨシヒロ; 日高, 秀夫; ヒダカ, ヒデオ; 立川, 涼; タツカワ, リョウ; 宮崎, 信之; ミヤザキ, ノブユキ; Fujise, Yoshihiro; Hidaka, Hideo; Tatsukawa, Ryo; Miyazaki, Nobuyuki (1985)
P(論文) 第22次日本南極地域観測隊の研究課題の一つとして, 1981-1982年に捕獲した5頭のウェッデルアザラシ(Leptonychotes weddelli)の外部形態ならびに臓器重量の測定結果を報告する。 External measurements and organ weights of five Weddell seals (Leptonychotes weddelli) collected under a project of the 22nd Japanese Antarctic Research Expedition in 1981-1982 are presented. departmental bulletin paper